Analysis on the influence social media marketing towards purchasing decision among students Universiti Malaysia Kelantan in Pengkalan Chepa - Fong Chui Theng; Intan Shafinaz Yusof; Nur Shahirah Saufi; Ummi Uffiya Sempul Amizam (2024)
Globally, social media has occupied an important position as a communication tool. People all over the world use social media to connect with other people or organizations. They also started using social media such as Facebook, Twitter, Instagram and LinkedIn to share their experiences. As customers, people share product reviews, information about services, advice about food or health, warnings about products, tips on using certain products and more. Social media is a powerful influence in the world of e-commerce. The objective of this study is to examine the influence of social media marketing towards purchasing decisions among students at Universiti Malaysia Kelantan in Pengkalan Chepa. There are 4 factors examined which are advertising, content, engagement, trend utilization. The research used a "convenience sampling" to collect the sample. Besides, 357 valid responses were collected from UMK students through an online google form consisting of four main sections which are A, B, C, and D. The IBM SPSS was used to analyze the data that had been obtained. The result has clearly shown that advertising, content, engagement, trend utilization had a significant relationship on the influence of social media marketing towards purchasing decisions among students at Universiti Malaysia Kelantan in Pengkalan Chepa. Thus, H1, H2, H3 and H4 were accepted because advertising, content, engagements, and trend utilization have significant relationships with purchasing decisions. Also, the study's implications, limitations and recommendations for further research were examined.